ASK-to-PSK generation based on nonlinear microring resonators coupled to one MZI arm - Tanaram, C.; Teeka, C.; Jomtarak, R.; Yupapin, P. P.; Jalil, M. A.; Amiri, I. S.; Ali, J. (My University, 2011)
We present a new concept of ASK-to-PSK generation based on nonlinear microring resonators coupled to one MZI arm by using OptiWave FDTD method. By microring resonator increase from one to three microring (SR to TR), we found that the amplitude shift keying (ASK) are increase exactly and the phase shift keying (PSK) is equal to π.
Keywords: ASK; Nonlinear microring resonators; PSK